Identity capital and future concerns in urban adolescents from La Araucanía-Chile - Neira-Escalona, Yosyua; Bravo-Sanzana, Mónica; Terán-Mendoza, Oscar; Miranda, Rafael (Frontiers in Education, 2024)
Introduction Late modernity influences the construction and constitution of identity and the management of adolescents’ future lives. Research has shown that identity capital predicts the resolution of a successful identity; however, in Latin America, no antecedents have conducted studies under this conceptual framework. Aim To analyze the relationship pattern between identity capital components and future concerns. Methods The participants were 703 adolescents between the ages of 15 and 19 years who, in the year 2021, were in the third and fourth years of high school in urban educational establishments in La Araucanía Chile, to whom questions from the Governance of Educational Trajectories in Europe (GOETE) adapted to the Chilean context and the general self-efficacy scale were applied. Confirmatory Factor Analyses (CFA) were performed to determine the suitability of the indicators to measure the constructs of interest and a structural equation analysis to determine the pattern of relationships between variables. Results The final model obtained excellent indicators of the goodness of fit [χ2 (422) = 965.858, p < 0.001; CFI = 0.977; TLI = 0.975; RMSEA = 0.043; SRMR = 0.056], in which it is evident that parental support and interaction are related to self-efficacy and self-concept and these, in turn, is associated with adolescents’ future concerns. Conclusion The relationship pattern tested shows that associations between tangible elements at the family level are related to intangible aspects of a personal nature, which can be protective factors against future concerns, and provide empirical support for the psychometric usefulness of the GOETE indicators in the Chilean context.